The Application of Hypnosis Schema Therapy in the Treatment of Women with Childhood Phobia Sexual - Honarparvaran, Nazanin (Psychology of Woman Journal, 2020)
This research was conducted to explain the effectiveness of hypnotic schema therapy in women suffering from sex phobia caused by childhood abuse in order to correct incompatible schemas and perform sexual intercourse. This research was conducted in the form of a case study using the A-B-A-B multi-baseline method with a one-month follow-up to ensure the effectiveness of the treatment on four women with sex phobia who were selected through available sampling for three months in 15 sessions. The improvement index was the downward trend of the curve compared to the baseline. These indicators were measured by semi-structured interview tools, sexual anxiety self-assessment scale and sexual dysfunction beliefs questionnaire (Nobre, Gouveia, and Gomez, 2003), and sexual intercourse success or failure diary. In the research results, the improvement index in the variables of sexual anxiety and sexually incompatible beliefs were observed, a downward trend compared to the treatment baseline, and the subjects were able to have sexual intercourse.